Kebijakan Pertanahan Larangan Pemecahan Hak Milik Atas Tanah Lebih dari Lima Bidang - Dwi Murti Hariani (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2018)
The purpose of this research is to study and analyze State Policy in the field of land concerning the prohibition of splitting land more than five fields. Research results The policy of prohibition of land ownership of more than five fields with a total area of 5000m2 has not been implemented maximally by both the parties involved and the community because the policy is not effective where the policies made are not accompanied by legal sanctions for those who violate the provisions. The National Land Agency only relies on a Statement from the applicant who wants to register his land at the local Land Office, which cannot be ascertained. The BPN has not yet made an inventory of how many parcels of land have been registered in the office, so that the list of individual land tenure has not been detected. Therefore, until now it has not been known how many people have owned land in excess of the provisions of the five fields with a total area of 5000m2.